REVENUE SHARING DALAM PRAKTEK LEMBAGA KEUANGAN SYARIAH DI INDONESIA - Arif Zunaidi; Fachrial Lailatul M (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2018)
Revenue sharing is the mechanism of the profit sharing principle that is now the concern of many people about the existence of Islamic banking which is something new after the Prophet's death, so that a problem arises, is revenue sharing in accordance with maqashid sharia ?. Whereas maqashid sharia is an important basis in formulating Islamic economics which includes Islamic Financial Institutions (LKS) / Islamic Banking. Responding to these questions DSN MUI issued a fatwa number 15 in the year 2000 concerning the principle of distribution of business results in Islamic financial institutions. By using this descriptive-interpretive method, it is intended to find out how revenue sharing is in the maqashid sharia perspective, by giving a whole and systematic picture as a whole. So that, it can be seen that revenue sharing with the issuance of the DSN MUI fatwa on the ability to run a revenue sharing system in Islamic Financial Institutions (LKS) / Islamic Banking is based on several verses of Al-Qur'an and Hadith, and Fiqhiyah Rules.